2001
DOI: 10.1007/s004310100763
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of the serum surfactant protein D and KL-6 levels in patients with measles complicated by interstitial pneumonia

Abstract: Surfactant protein D and KL-6 are easily measured and useful markers for the diagnosis of interstitial pneumonia caused by measles infection. Early decrease of surfactant protein D contrasts with the transient increase of KL-6 levels after prednisolone pulse therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 12 publications
0
20
1
Order By: Relevance
“…reported that all of the deceased patients had serum KL‐6 levels of more than 2000 U mL −1 , and that no patients with KL‐6 levels of <1000 U mL −1 died [30]. By contrast, it should be noted that the patients in the present study were patients with the most usual slowly progressive ILD, rather than the rapidly deteriorating patients who had been reported in those previous studies [10, 13, 28–30]. Therefore, the optimal cut‐off level, which we recommend, is apparently different from that for such acute clinical conditions.…”
Section: Discussionmentioning
confidence: 54%
“…reported that all of the deceased patients had serum KL‐6 levels of more than 2000 U mL −1 , and that no patients with KL‐6 levels of <1000 U mL −1 died [30]. By contrast, it should be noted that the patients in the present study were patients with the most usual slowly progressive ILD, rather than the rapidly deteriorating patients who had been reported in those previous studies [10, 13, 28–30]. Therefore, the optimal cut‐off level, which we recommend, is apparently different from that for such acute clinical conditions.…”
Section: Discussionmentioning
confidence: 54%
“…KL‐6 and SP‐D are both derived from type II alveolar epithelial cells and their elevation in serum reflects alveolar epithelial cell injury 9 . In severe measles pneumonia, for example, serum SP‐D elevation precedes KL‐6 elevation 12 . This is explained by the fact that SP‐D has a very small molecular weight (43 kD) and passes through the alveolar–capillary fenestration from the early period of alveolar involvement, while KL‐6, which has a large molecular weight (200 kD), cannot pass through the fenestration and rises in a later phase 13 .…”
Section: Discussionmentioning
confidence: 99%
“…SP‐D has antiviral defense activity and modulates innate and adaptive immunity 14 . KL‐6, as well as SP‐D, is a good biomarker for interstitial lung diseases among children 2,10,12,15,16 . They are both useful for diagnosis and for assessing disease severity 10,12,15 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, experimental studies have emphasized that specific pulmonary bioindicators considered to be secreted from deteriorated lung tissue, such as surfactant protein A (SP-A), surfactant protein D (SP-D), Krebs von den Lungren-6 (KL-6), and Clara cell protein (CC-16), are effective in determining lung deterioration severity (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%